2019
DOI: 10.7717/peerj.7594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shading on the growth and leaf photosynthetic characteristics of three forages in an apple orchard on the Loess Plateau of eastern Gansu, China

Abstract: Background Inclusion of forage into the orchard is of great help in promoting the use efficiency of resources, while shading from trees restricts forage growth and production in the Loess Plateau of China. This study was aimed to investigate how tree shading affected leaf trait, photosynthetic gas exchange and chlorophyll feature of forages under the tree in the orchard-forage system. Methods The shading treatments were set as partially cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…be that shade could help plants maintain soil moisture, improve the air humidity around plants, and help plants resist possible water stress, especially in the semiarid area (Yang et al 2019). In this study, we found that shading environment inhibited leaf photosynthesis parameters.…”
Section: Discussionmentioning
confidence: 53%
“…be that shade could help plants maintain soil moisture, improve the air humidity around plants, and help plants resist possible water stress, especially in the semiarid area (Yang et al 2019). In this study, we found that shading environment inhibited leaf photosynthesis parameters.…”
Section: Discussionmentioning
confidence: 53%
“…Similar tendencies were reported by Lopez-Marin et al [67], with a negative correlation between shade levels and WUE in a greenhouse experiment with sweet pepper plants, in which the highest values were registered under non-shaded conditions. In addition, Yang [68] found similar tendencies in forages. In cacao growing under high and low PPFD, Jaimez et al [66] found that WUE showed a negative linear relationship with light level.…”
Section: Physiological Parameters Influenced By Shadementioning
confidence: 77%
“…Similar tendencies were reported by Lopez-Marin et al [66], with a negative correlation between shade levels and WUE in a greenhouse experiment with sweet pepper plants, registering the highest values under non-shaded conditions. Also, Yang [67] found similar tendencies in forages. Jaimez et al [65] found in cacao growing under high and low PPFD that WUE showed a negative linear relationship with light level.…”
Section: Physiological Parameters Influenced By Shadementioning
confidence: 62%